Multi-surface and bounding surface models in hyperplasticity. (April 2023) - Houlsby, G.T.; Richards, I.A.
Abstract: We develop a series of models of the bounding surface type within the context of hyperplasticity theory, in which models are completely defined by the specification of two potentials. We first describe a simple bounding surface type model, based on an equivalent multi-surface model, but with the advantages that (a) only a single yield surface is required and (b) a smooth rather than piecewise linear response is achieved. We then generalise this model in a way that allows it to be calibrated against real data with similar facility to a multi-surface model. Each model is presented in a simple one dimensional form, with generalisations to two dimensions and to a full tensorial form. Finally we give an example of the newly developed model calibrated against a monotonic test, and present comparisons with one-way and two way cycling and two complex bi-directional tests.